Accumulation of terpenoid indole alkaloids in jasmonic acid elicited catharanthus roseus plants before and during flowering - Pan, Qi Fang; Saiman, Mohd Zuwairi; Verpoorte, Robert; Tang, Kexuan (Pakistan Botanical Society, 2018)
Jasmonates analogues including jasmonic acid (JA) and methyl-jasmonate (MeJA) are plant-signaling molecules involved in defense against insects and pathogens. In Catharanthus roseus, jasmonates play a key role in regulating the biosynthesis of pharmaceutically important terpenoid indole alkaloids (TIAs). In the present study, C. roseus plants were elicited with JA before and during flowering to investigate the induction of TIA biosynthesis in different organs during the two developmental stages concerning via HPLC and qRT-PCR methods. The results showed that JA stimulates the TIA accumulation before flowering but had less effect during flowering. TIA accumulations in different organs (flower, leaf, and root) also showed a different response to JA elicitation. Moreover, transcriptional analysis showed that JA elicitation had a greater effect on the expression levels of key TIA biosynthetic genes (such as STR, SGD, DAT and PRX1) in C. roseus before flowering than during flowering. In C. roseus control (non-treated) plants the level of jasmonic acid was higher before flowering than during flowering, and in JA-treated plants JA was accumulated more before flowering than during flowering. The study provided an insight into the effect of flowering on JA-induced TIA biosynthesis in C. roseus plants.